Representations of palliative care, euthanasia and assisted dying within advocacy declarations. (2nd April 2020) - Inbadas, Hamilton; Carrasco, José Miguel; Clark, David
ABSTRACT: It is well known that there are disagreements between the proponents of palliative care and of euthanasia or assisted dying, often with little common ground, shaping the end of life discourse internationally. Advocacy documents or 'declarations'constitute a significant feature of this discourse. The aim of this study was to explore the content of such declarations and to focus on what they can tell us about palliative care and assisted dying and their dispositions towards one another. 104 declarations were identified and included in the study, covering the period 1974 to 2017. These declarations were analysed following the principles of thematic content analysis. We classified them based on their primary purpose: those with the goal of advocating for palliative care services, education and research were grouped under 'palliative care declarations'; those with the primary objective of advocating for or against euthanasia/assisted dying were classified as "euthanasia/assisted dying declarations". Our analysis revealed that the content of the declarations could be broadly categorised into three dimensions: framing, claiming and demanding. We demonstrate that these declarations reveal a struggle over the construction of meanings relating to palliative care and assisted dying and constitute a valuable resource for the analysis of an unfolding debate.